2020
DOI: 10.3390/app10051581
|View full text |Cite
|
Sign up to set email alerts
|

A Parametric Study of the Acoustic Performance of Resonant Absorbers Made of Micro-perforated Membranes and Perforated Panels

Abstract: Sound absorbing surfaces are being increasingly requested for the acoustical treatment of spaces, like offices and restaurants, where high aesthetic standards are requested. In these cases, perforated and micro-perforated panels may represent the ideal solution in terms of low maintenance, durability, and mechanical resistance. In addition, such a solution might be conveniently realized while using optically transparent panels, which might offer extra value, as they could ensure visual contact, while remaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Although it is not related to 3D printing, Pan and Martellotta [15] performed trial productions of MPP with films of 5.0 mm thickness with microdrills. The hole diameter of their specimens showed a Gaussian distribution from 0.2 to 0.35 mm around the targeted value of 0.3 mm.…”
Section: Sound Absorption Performance Of Mpps and Manufacturing Accuracymentioning
confidence: 99%
“…Although it is not related to 3D printing, Pan and Martellotta [15] performed trial productions of MPP with films of 5.0 mm thickness with microdrills. The hole diameter of their specimens showed a Gaussian distribution from 0.2 to 0.35 mm around the targeted value of 0.3 mm.…”
Section: Sound Absorption Performance Of Mpps and Manufacturing Accuracymentioning
confidence: 99%
“…More recently, in a case study on the absorption characteristics of an MPP with distributed hole diameters due to the lower production accuracy, Pan and Martellotta showed that a relatively good prediction of absorption characteristics was possible using the mean hole diameter in the case that the deviation is smaller [15]. On the contrary, Sakagami et al [16] reported a case study of MPPs produced by a 3D printer of nonprofessional use, in which hole diameters were distributed randomly due to the lower production accuracy: It was shown that the predicted values, using the mean hole diameter as the representative diameter in the existing theory, were not in good agreement with the measured results.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the interest in sound absorbing materials is growing due to the variety of their possible applications, from room acoustics [1] to environmental noise control [2,3]. Porous and fibrous absorbers [4][5][6] have until now been the most used materials in noise control application because of their high performance-to-cost ratio in the frequency band of interest.…”
Section: Introductionmentioning
confidence: 99%